Consumer grief: understanding how consumers deal with the loss of extraordinary experiences - Fernanda Scussel; Maribel Carvalho Suarez (Cadernos EBAPE.BR, 2022)
Abstract Despite the interest in the role of consumption in the bereavement process, the concept of consumer grief and the process consumers experience when grieving remain undertheorized. This article aims to conceptualize consumer grief considering the disruption brought by the COVID-19 pandemic and the need to understand how consumers respond to this scenario, understanding the mechanisms consumers create to deal with loss. In view of the importance of extraordinary experiences due to their embodied, social, and transformational power, in this netnographic study, we explore marathon runners’ loss of an extraordinary experience. Consumers deal with the loss of an experience through a process composed of five mechanisms mediated by social media, which enable consumers to reverse, reframe, and reestablish the experience. The mechanisms of refutation, despair, abstention-compensation, transgression, and acceptance show how consumers behave in different moments of grief, allowing them to build their trajectories in the grieving process, individually and collectively. As a contribution, we expand the literature on consumer grief by focusing on the specific concept of consumer grief, explaining the processes consumers go through when they deal with the loss of an experience. Additionally, we present a collective perspective on the grieving process, shifting the analysis of the grief of an individual or a family unit to the socialization of grief.